Решить уравнение x-0,5-(x-0,5x)*0,4=3

oDESo oDESo    3   20.10.2020 01:38    0

Ответы
Рома3108 Рома3108  19.11.2020 01:40

х-0,5-(х-0,5х)×0,4=3

х-0,5-0,5х×0,4=3

х-0,5-0,2х=3

0,8х-0,5=3

0,8х=3+0,5

0,8х=3,5

х=4,375

ПОКАЗАТЬ ОТВЕТЫ
Аня276541 Аня276541  19.11.2020 01:40

ответ: 4,375

Пошаговое объяснение:

х - 0,5 - (х - 0,5х) * 0,4 = 3

х - 0,5 - 0,4х + 0,2х = 3

х - 0,4х + 0,2х = 3 + 0,5

0,6х + 0,2х = 3,5

0,8х = 3,5

х = 3,5 : 0,8

х = 4,375

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика